The relationship between semantic access and introspective awareness - Xu, Xu; Kang, Chunyan; Pascucci, David; Guo, Taomei (Brain and cognition, 2018)
•Evidence is reported for association of introspective awareness and semantic access.•Awareness self-reports relate to neurophysiological processes of semantic system.•Findings may contribute to the search for neural basis of higher order consciousness. There have long been speculations about the relationship between consciousness and language. This study aimed to determine whether an individual’s level of introspective awareness, based on self-report, relates to accessibility of their semantic system as evaluated by the N400. Thirty-five university students completed the study. All were right-handed, with normal or corrected-to-normal vision, without known neurological or psychological health issues. They first performed on a lexical decision task while their brain electrophysiological responses were recorded. Then, they provided assessment ratings about their levels of introspective awareness. Analysis revealed moderate to strong correlations (Pearson’s rs = 0.49–0.62) between awareness self-ratings and ease of semantic access as indexed by the N400. Correlation between the self-report measure and the objective neurophysiological measure suggests that subjective assessment of awareness may deserve more credibility, which in addition to reflecting subjective perception and evaluation about one’s own higher order mental functioning, may also interact with the neurophysiological processes contributive and subject to such awareness. Implications for future research on the role of semantic network in the mechanism of introspective awareness are discussed.